2007
DOI: 10.1073/pnas.0702621104
|View full text |Cite
|
Sign up to set email alerts
|

A semiquinone intermediate generated at the Q o site of the cytochrome bc 1 complex: Importance for the Q-cycle and superoxide production

Abstract: The cytochrome bc1 and related complexes are essential energyconserving components of mitochondrial and bacterial electron transport chains. They orchestrate a complex sequence of electron and proton transfer reactions resulting in the oxidation of quinol, the reduction of a mobile electron carrier, and the translocation of protons across the membrane to store energy in an electrochemical proton gradient. The enzyme can also catalyze substantial rates of superoxide production, with deleterious physiological co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
185
3
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 157 publications
(195 citation statements)
references
References 60 publications
(94 reference statements)
5
185
3
2
Order By: Relevance
“…With those considerations, the experiments depicted in Figure 2 establish a broad range of conditions under which the sustained influx of electrons into heme b L cannot be balanced with the outflow of electrons from this heme to heme b H (Figure 1d,e). This traps heme b L in the reduced state which is expected to increase the probability of uncoupling of the FeS-and heme b L -mediated two-electron oxidation/reduction of quinol/ quinone at the Q o site and result in the formation of semiquinone (SQ o ) (22,31). The highly unstable SQ o is then expected to be able to reduce oxygen generating superoxide.…”
Section: Steady-state Properties Of Cofactor Knockoutsmentioning
confidence: 99%
See 1 more Smart Citation
“…With those considerations, the experiments depicted in Figure 2 establish a broad range of conditions under which the sustained influx of electrons into heme b L cannot be balanced with the outflow of electrons from this heme to heme b H (Figure 1d,e). This traps heme b L in the reduced state which is expected to increase the probability of uncoupling of the FeS-and heme b L -mediated two-electron oxidation/reduction of quinol/ quinone at the Q o site and result in the formation of semiquinone (SQ o ) (22,31). The highly unstable SQ o is then expected to be able to reduce oxygen generating superoxide.…”
Section: Steady-state Properties Of Cofactor Knockoutsmentioning
confidence: 99%
“…This, however, may change when the impeded electron flow outbalances reducing equivalents in the two chains, which has long been known from the classic experiments with an inhibitor antimycin which demonstrated that blocking specifically the electron flow through the Q i site is sufficient to make the enzyme vulnerable to superoxide production (10, 11). These kinds of observations have raised an ongoing debate about whether cytochrome bc 1 does produce superoxide in living cells (12)(13)(14)(15)(16) (5,(17)(18)(19)(20)(21)(22)(23)(24). Answering those questions not only would bring clarity to many physiological and medical studies but also should improve our understanding of the molecular mechanisms of energy conservation supported by cytochrome bc 1 .…”
mentioning
confidence: 99%
“…One might therefore expect that MKcontaining organisms simply ''take advantage'' of this additional driving force and get along with a single, UQ-type bc 1 complex. However, it has recently been shown that conservation of the Q-cycle driving force is critical to preventing deleterious superoxide production at the Q O site (32)(33)(34)(35). Substitution of the LP rhodoquinol (RQH 2 ) for UQH 2 in mitochondrial cyt.…”
Section: Evolutionary Driving Forces Favoring the Presence Of 2 Distimentioning
confidence: 99%
“…The interaction between cytochrome c1 (cyto.c1) and cyto.c ensures the fast complex formation, optimal orientation and distance for electron transfer and also fast dissociation after electron transfer, which is critical for maintaining the electron flow and preventing the potential electron leak [4,5]. The cytochrome bc1 complex is also the major pathway for free radical generation within mitochondria [6][7][8]. Disruption of this interaction results in the loss of the oxidative phosphorylation, ample generation of reactive oxygen species (ROS) and disruption of mitochondrial functions and physiology leading to cell death.…”
Section: Introductionmentioning
confidence: 99%